Multi-endpoint analysis of cadmium chloride-induced genotoxicity shows role for reactive oxygen species and p53 activation in DNA damage induction, cell cycle irregularities, and cell size aberrations - Katherine Chapman (Mutagenesis, 2024)
Cadmium chloride (CdCl2) is a known genotoxic carcinogen, with a mechanism of action thought to partly involve the generation of reactive oxygen species (ROS). We applied here a multi-endpoint approach in vitro to explore the impact of CdCl2 on both the genome and on wider cell biology pathways relevant to cancer. Multi-endpoint approaches are believed to offer greater promise in terms of understanding the holistic effects of carcinogens in vitro. This richer understanding may help better classification of carcinogens as well as allowing detailed mechanisms of action to be identified. We found that CdCl2 caused DNA damage (micronuclei; MN) in both TK6 and NH32 cells in a dose dependent manner after 4 hours exposure (plus 23 hours recovery), with lowest observable effect levels (LOELs) for MN induction of 1μM (TK6) and 1.6μM (NH32). This DNA damage induction in TK6 cells was ROS dependent as pre-treatment with the antioxidant N Acetyl Cysteine (1mM), abrogated this effect. However, DCFDA was not capable of detecting the ROS induced by CdCl2. The use of NH32 cells allowed an investigation of the role of p53 as they are a p53 null cell line derived from TK6. NH32 showed a 10-fold increase in MN in untreated cells and a similar dose dependent effect after CdCl2 treatment. In TK6 cells, CdCl2 also caused activation of p53 (accumulation of total and phosphorylated p53), imposition of cell cycle checkpoints (G2/M) and intriguingly the production of smaller and more eccentric (elongated) cells. Overall, this multi-endpoint study suggests a carcinogenic mechanism of CdCl2 involving ROS generation, oxidative DNA damage and p53 activation, leading to cell cycle abnormalities and impacts of cell size and shape. This study shows how the integration of multiple cell biology endpoints studied in parallel in vitro can help mechanistic understanding of how carcinogens disrupt normal cell biology.